THE EFFECTIVENESS OF EXPERIENTIAL LEARNING PROGRAM WITH DESIGN THINKING ON ENHANCING INNOVATION BEHAVIOR AMONG PRE-SERVICE MUSIC AND DANCE TEACHERS, BUNDITPATANASILPA INSTITUTE OF FINE ARTS - Anodas, Panjaporn; Peungposop, Narisara; Prayai, Narulmon (Journal of MCU Nakhondhat, 2026)
This research article aimed 1) To explore and understanding the meaning, causes, and learning management approaches that promote innovative behaviour among pre-service music and dance teacher students. 2) To examine the effectiveness of an experiential learning programme integrated with design thinking in enhancing innovative behaviour among pre-service music and dance teachers. The study employed a pre-experimental research design using a one-group pretest–posttest approach. The population consisted of undergraduate pre-service teachers in the fields of Music and Dance, and the sample was obtained through simple random sampling, comprising 38 participants. The research instruments consisted of two components. The first was an experiential learning program integrated with the design thinking approach, designed to actively engage learners through hands-on activities, reflective practices, and creative problem-solving processes. The second was an innovative behavior scale for pre-service teachers. Both instruments were examined for content validity by a panel of experts, with item-objective congruence values ranging from 0.80 to 1.00. The innovative behavior scale demonstrated high reliability, with a Cronbach’s alpha coefficient of 0.92. Data analysis involved descriptive statistics, including mean and standard deviation, to summarize participants’ innovative behavior levels. Inferential statistics were applied using a paired-samples t-test to compare innovative behavior scores of control group and experiment group participation in the program. The findings revealed that after participating in the experiential learning program integrated with the design thinking approach, the pre-service teachers exhibited significantly higher innovative behavior scores than those obtained prior to the intervention, at the .05 level of statistical significance. The results indicate that the program was effective in enhancing innovative behavior among pre-service teachers in Music and Dance. In conclusion, integrating experiential learning with design thinking provides an effective instructional approach for fostering innovative behavior in teacher education. The program can be applied as a practical guideline for improving teaching and learning management in arts teacher education institutions and is consistent with the educational demands of the twenty-first century worldwide today broadly.